IMPACT OF CONTEXTUAL LEARNING ON RETENTION OF KNOWLEDGE - Nasreen, Maimoona; Janjua, Qasim M.; Leghari, Qurrat-ul-ain; Malik, Samina (Pakistan Journal of Physiology, 2018)
Background: Case stimulated learning approach provides a link between basic and clinical sciences. Learning in a contextual clinical situation motivates the students and has a positive impact on their assessment. The objective of this study was to assess the effectiveness of interactive and case stimulated teaching of endocrine physiology to medical students at the University of Lahore. Methods: In this comparative cross-sectional study, a total of 260 second year medical students of 2014 and 2015 batches were included through convenience sampling. In the first batch, a total of 137 students (43 males and 94 females) were offered interactive endocrinology lectures. Whereas, in the second batch, a total of 123 students (55 males and 68 females), were exposed to case stimulated teaching by the same facilitator. Multiple-choice questions were used to assess the students before and after the teaching sessions. The results of both sessions were analyzed by Student’s t-test. Results: Students who were taught through case stimulated methodology performed better during examination as compared to those who were taught through conventional methodology (19.8±0.4 vs 13.5±0.3, p<0.001). Conclusions: Students retain knowledge for a longer time when it is relevant and applicable to clinical context. Use of case stories in classrooms promotes better understanding, and the question and answer activity helps in making critical decisions in clinical practice. Case stimulated learning strategy can be adopted not only to enhance academic performance but also to promote contextual learning. Pak J Physiol 2018;14(2):43–5